Who Gets to Talk About NGO Images of Global Poverty?. (3rd July 2019) - Ademolu, Edward; Warrington, Siobhan
Abstract: Ademolu and Warrington are social science researchers who have used photographs and films to explore the experiences and perspectives of those absent from the debates on visual representations of global poverty. This article engages in a discussion about their respective research projects, The People in the Pictures (Warrington and Crombie2017 ) and Rethinking Audiences (Ademolu 2018). It explores the backgrounds to their projects and their experiences of using images as a research tool, and considers how their research contributes to ongoing debates about NGO communications and representations of global poverty. The impetus, experience and findings of their respective research seek to provoke those involved in NGO image making (practitioners and researchers) to ask themselves if the perspectives of all those involved are being considered, especially those communities who are the subject of representation, either directly in images or more indirectly through diaspora connections to the represented communities. It argues for a shift in both the debates and NGO image making itself, towards more inclusive dialogue and practice.